Therapeutic Effect of Calcipotriol Pickering Nanoemulsions Prepared by Exopolysaccharides Produced by Bacillus halotolerans FYS Strain on Psoriasis - Wang Y (Dove Medical Press, 2020)
Yuzhen Wang,1 Hong Li,2 Fakun Dong,3 Fang Yan,3 Min Cheng,4 Wanzhong Li,3 Qi Chang,3 Tianzi Song,3 Aoying Liu,3 Bo Song3 1Medical Imaging Specialty, Weifang Medical University, Weifang, Shandong, People’s Republic of China; 2Basic Medical School, Weifang Medical University, Weifang, Shandong, People’s Republic of China; 3School of Pharmacy, Weifang Medical University, Weifang, Shandong, People’s Republic of China; 4Clinical Medical College, Weifang Medical University, Weifang, Shandong, People’s Republic of ChinaCorrespondence: Bo SongWeifang Medical University, Baotong Street, No. 7166, Weifang, Shandong 261053, People’s Republic of ChinaTel/Fax +86-536-8462490Email songsbob@163.comPurpose: Many exopolysaccharides (EPS) have significant emulsifying activity. Some EPS produced by the marine bacterial strain FYS have stronger emulsifying activity in the form of nanoparticles, suggesting that they could potentially form Pickering emulsions. We prepared novel EPS/CT Pickering nanoemulsions (ECPN) with EPS as emulsifiers and assessed their ability to ameliorate the poor permeability of calcipotriol (CT) in skin affected by psoriasis vulgaris.Methods: A strain of marine bacterium FYS was identified. Molecular weight, monosaccharide composition and microstructure of EPS were determined by gel permeation chromatography, high-performance liquid chromatography and scanning electron microscopy. EPS nanoparticles were prepared by adjusting the pH, and the emulsifying activity was studied at different pH. ECPN were prepared by ultrasound and optimized by the response surface method. The size distribution, microstructure, stability and in vitro drug release of ECPN were studied. The therapeutic effect of ECPN on psoriasis vulgaris was explored by animal experiments and characterizing histomorphology in vivo.Results: A phylogenetic tree revealed that FYS was a Bacillus halodurans strain. EPS produced by the strain were heteropolysaccharides with a three-dimensional network composed of glucose, galactose, glucuronic acid, rhamnose, galacturonic acid and mannose (32.0:34.3:9.7:7.4:10.3:6.3). The EPS can form nanoparticles at pH = 4– 6 with enhanced emulsifying ability. Transmission electron microscopy revealed that EPS nanoparticles adhered to the surface of oil droplets to stabilize the emulsions via a Pickering emulsification mechanism. The prepared ECPN have high stability with a sustained-release effect. Finally, animal experiments showed that ECPN effectively shortened the treatment course of psoriasis vulgaris.Conclusion: EPS is highly possible to have the potential Pickering emulsification mechanism. The stability of the nanoemulsion was high. ECPN also showed potential for use in the treatment of psoriasis vulgaris. This study provides new insight into the medical applications of EPS and the treatment of psoriasis.Keywords: Bacillus halotolerans, exopolysaccharides, response surface method, psoriasis